Molecular disorders of erythrocyte and platelet membranes in vascular complications of type 1 diabetes mellitus - Ye. B. Kravets; N. V. Ryazantseva; N. M. Yakovleva; V. N. Butusova; O. M. Choudakova; E. V. Saprykina (Бюллетень сибирской медицины)
The aim of the present study was to establish the role of disturbances of structural-functional properties of erythrocyte and platelet membranes in mechanisms of development and progression of vascular complications of type 1 diabetes. The subjects were 92 patients (48 men and 44 women, aged from 18 to 55) affected by type 1 diabetes in different stages of diabetic retinopathy and diabetic nephropathy. The results have shown the significant structural and functional changes of red blood cells and platelet membranes in type 1 diabetes mellitus. These changes (increase of microviscosity of lipid phase, inhibition of Na+,K+-АТPase activity) correlated with the degree of expression of vascular complications. Since the rheologic properties of blood cells, particularly its microrheologic features, are determined by the membrane status, the detection of changes in the molecular organization of erythrocyte and platelet membranes can be consider as a pathogenic link of diabetic microangiopathies.